Effect of UV-ozone process on the ZnO interlayer in the inverted organic solar cells. Issue 10 (18th January 2017) - Li, Dou; Qin, Wenjing; Zhang, Shengchen; Liu, Dongyue; Yu, Zhenyang; Mao, Jing; Wu, Linfeng; Yang, Liying; Yin, Shougen
Abstract : Free oxygen atoms generated by UV-ozone treatment penetrates into ZnO lattices and then cause the decrease of oxygen vacancy and increase of oxygen interstitial defects. The revolution affects the WFs of ZnO and finally the properties of IOSC. Abstract : ZnO interlayer is crucial for the performance of inverted organic solar cells (IOSCs). Herein, we investigate the effects of short UV-ozone treatment of ZnO nanofilms (ZnONFs) on the performance of IOSCs with a structure of ITO/ZnONFs/P3HT:PCBM/MoO3 /Ag. There is a 17.59% and 32.60% increase in the short circuit current and power conversion efficiency, respectively, after the treatment of the device for 20 seconds. Furthermore, the optimized device showed excellent stability under ambient conditions for more than four weeks without encapsulation. We conclude that the UV-ozone treatment oxidizes oxygen vacancy defects of ZnONFs, thereby decreasing the internal resistance and improving charge transfer at the ZnONFs/polymer interface. However, a longer treatment time will produce oxygen interstitial defects, which dramatically increases the work functions of ZnONFs and deteriorates the contact between ZnONFs and the active layer. As a result, the process of charge transfer will be blocked, resulting in a sharp drop in the performances of IOSCs.